Review Article: Metformin-Associated Lactic Acidosis - จักรเมธากุล รจนา (Journal of Preventive Medicine Association of Thailand, 2018)
Although metformin has become a drug of choice for the treatment of type 2 diabetes mellitus, a serious condition called metformin-associated lactic acidosis (MALA) can occur in patients with predisposing factors such as renal insufficiency, hepatic disease, congestive heart failure, or sepsis. The incidence of lactic acidosis in patients on metformin therapy appears to be very low, but it can be fatal when it occurs. Mortality is not correlated with lactate or metformin levels but the factors associated with fatal outcomes including high APACHE II score, the presence of shock, the requirement for mechanical ventilation and vasopressors. Prompt recognition of lactic acidosis and early treatment using hemodialysis can result in a favorable clinical outcome, especially in patient has severe metabolic acidosis (pH< 7). To prevent MALA, risk factors should be carefully assessed and intimately monitored in renal function.